Kajian Potensi Turbin Angin Sumbu Horizontal Menggunakan Metode Simpangan Baku Distribusi Weibull - Fauzan, Dimas Muhammad (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study evaluates the wind energy potential in West Kalimantan by utilizing annual wind speed data from the Meteorology, Climatology, and Geophysics Agency (BMKG) Supadio Pontianak, recorded from January 1 to December 31, 2024. The analysis applies the standard deviation method within the Weibull distribution to determine the shape k and scale c parameters, which are subsequently used for estimating the annual energy output of a wind turbine. Research procedures include secondary data collection, wind speed data processing, statistical analysis, Weibull parameter estimation, model validation using Mean Absolute Error (MAE), and energy potential calculation based on the turbine power curve. Results show that the average wind speed is 5.11 knots (2.63 m/s) with a standard deviation of 2.96 knots, resulting in k=1.8182 and c=5.7726 knots. The Weibull model fits the observed data well, with an MAE of 0.06666. The Aeolos-H 3 kW turbine was chosen as a case study, showing an estimated annual energy production of 261.890 kWh. These findings demonstrate that even under low to moderate wind conditions, properly selected turbines can generate meaningful electricity output. This study provides insights for small-scale renewable energy development and supports technology selection for wind power generation in low-wind-speed regions of Indonesia.